أساليب التشبيه في سورة آل عمران ودلالتها الدعوية - Ade Juang Eko Praseyo; ANWAR, SAEFUL; Tamam, Abas Mansur; Alim, Akhmad (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2023)
The aim of studying this topic is to know the implications of the tashbehs mentioned in Surah Al-Imran related to the da’wah aspect. In carrying out this research, the researcher used two scientific approaches, namely the analytical descriptive approach, and the deductive approach. These two approaches paved the way for the researcher to analyze the tashbehs in Surah Al-Imran, and then discover and deduce from those tashbeh meanings related to the da’wah side to be a da'wah approach method applied in the fields of Islamic advocacy. The study concluded that in Surah Al-Imran there are methods of tashbehs, and they carry moral connotations related to the da’wah aspect. These indications can be extracted from methods and modalities used as a methodology for the call to spread Islam in societies. By using tashbehs methods in the da’wah process, it will be better, because the da’wah materials are easier to understand and stronger to influence. Also, the tashbehs method enhances the emotional relationship between the da’e and the mad’o, and between the preacher and the listener, making the da’wah more acceptable to people. Thus, it can be said that the use of analogy as an advocacy tool has a positive impact on spreading the beauties of Islam in societies.